RADIOPROTECTION SURVEILLANCE OF THE TJ-II OPERATION BY TLD. Issue 12 (2nd July 2022) - Noguerales, C; Álvarez, A; Ascasibar, E; Carrasco, R; Liniers, M; Medrano, M; Rodríguez-Rodrigo, L; Vico, A
Abstract: The TJ-II stellarator presently in operation at the National Laboratory of Fusion is subject to radiological surveillance in compliance with the Spanish Nuclear Regulation. During its pulsed operation hard X-rays are emitted by the runaway electrons, and soft X-rays are generated by bremsstrahlung of thermalized electrons. Inside the experimental hall, the plasma heating systems and some active diagnostics are additional sources of radiation. Outside the experimental hall, some auxiliary systems, such as high-voltage power supplies, must be checked for radiological influence. In order to verify the adequate radiological classification of the different working areas, 15 dosemeters are distributed in radiologically controlled areas close to the machine, as well as in areas of public use in the TJ-II building. The integrated dose equivalent is analyzed to help establish the range of radiological influence of the stellarator. The results of the period 2015–20 are presented and analyzed.